Documented barriers to health care access among Latinx older adults: A scoping review. Issue 2 (1st February 2023) - Lee, Kathy; Cassidy, Jessica; Mitchell, Jaci; Jones, Sarah; Jang, Si Won
ABSTRACT: Latinx older adults experience poor access to health care services, resulting in a higher prevalence of physical and mental health issues and greater rates of disabilities. The purpose of this study was to map the literature regarding barriers impacting Latinx older adults' access to health care services. We conducted a scoping review of peer-reviewed journal articles from eligible U.S. studies. We selected 23 articles for the final review. Following a methodological framework for conducting scoping studies, we charted the selected articles in an Excel spreadsheet and synthesized by applying a content analysis approach. Then, we collated, summarized, and reported the results. Barriers discussed in the selected articles included language barriers, low levels of health literacy, fears or distrust for health care services or providers, stigma or negative attitudes toward health care services, lack of health care or disease-related information, low socioeconomic status, not having health insurance, expensive health care costs, and limited transportation options. To respond to underutilization of health care services among Latinx older adults, the findings from this review suggest that expanding community-based education, minimizing barriers to long-term care, and making outreach efforts can reduce unique barriers that Latinx older adults experience.